Application of Chatbot Using Chatbotika to Use Promote Product Business on the website of PT Services and Tourism West Java (Perseroda) - Ardhi Akmaludin Jadhira (Budapest International Research and Critics University, 2022)
One role important in the digital business era in operate business in the field of services and tourism in need interaction with customer is chatbots. Chatbot b isa said one key confidential in support digital marketing and improve customer experience. Customer experience is supporter most important in a business process. With existence customer experience in chatbot sales becomes more practical without need throw away time and resources power, because chatbot provide 24 hour service and chat can customized based on segmentation and scale the customer. Chatbots are also capable scan needed information and automate response with fast and precise. Technology chatbot built use chatbot. Chatbotika is designed chatbot with technology Artificial Intelligence (AI) capable of imitate conversation human and role as digital assistant. After chatbot succeed integrated with Website Company, next is with do a test conversation to chatbot based on intents that have been made. Test results the showing that chatbot capable for give response relevant answer based on based on question asked customer. From the range score 0 to 1 intent product tested get score 0.83, which proves that intent work with good.